Social representations of physical education teachers concerning the game: a qualitative study in Chile - Alejandro Almonacid-Fierro; Jessica Mondaca Urrutia; Sergio Sepúlveda-Vallejos; Karla Valdebenito (IP Iermakov S.S., 2021)
Background and Study Aim. The objective of this research was to determine the social representations of the game in physical education teachers belonging to the Chilean educational system, searching for the sense and meaning given by the educators to the game aspect. Material and Methods. The study sample consisted of 14 physical education teachers, who were chosen by the convenience sampling method. Semi-structured interviews were used to collect data from the participants, maintaining gender equity. The analysis of the data obtained was by means of content analysis and the NVivo 11 program was used to process the data. Results. Our research indicates that of the categories analyzed, the highest was the role of the game (22.29%), demonstrating the relevance given by teachers to the game in the development of meaningful learning. On the contrary, the category characteristics of the game (17.42%), describe how teachers visualize the contributions of play at the educational level, in this sense, the role of the game goes beyond motor contributions, but also provides tools for social and cognitive development. Conclusions. For the teachers, the game promotes autonomous and proactive actions of the students, which will be beneficial to understand that playfulness in education implies not to put in contradiction the rational and emotional faculties. This comprehensive view is called full attitude, and it is a relevant step toward the understanding of the game from a complex perspective. In this area, it is evident that, in the social representations of the participating teachers, the game constitutes a natural environment in which children develop, where the physical education teacher should create an environment that facilitates the game, facilitating the expression of autonomy, freedom, creativity, and playfulness.